Hygiene and Sanitation of Refill Drinking Water Depo at PT X, Taman, Sidoarjo - Triana Oktaviani (Universitas Airlangga, 2018)
PT X established a refill drinking water depo to produce drinking water independently and meet the liquid needs of employees to avoid being hydrated and exhausted due to the hot working climate. Hygiene sanitation of Drinking Water Refill Depo PT X needs to be considered because the condition is in the environment with various hazardous and toxic materials and hazardous and toxic materials waste.This research had purposed to know sanitation hygiene from drinking water content that is within the scope of industry PT X in Sidoarjo. This research was a observational research with cross sectional design. The subjects of the research were Drinking Water Refill Depo PT X Taman, Sidoarjo, with the number of respondents as many as 3 employees of Drinking Water Refills Depo. Data were collected by observation sheet as stated in Regulation of the Minister of Health of the Republic of Indonesia No. 43 of 2014 on Hygiene Sanitation Drinking Water Depo. Drinking Water Refill Deposit PT X does not meet the physical wellness requirements of drinking water Depos with a total score of 65 points. There is a number of disadvantages that need to be corrected in the condition of non-preserved buildings, unrefined Drinking Water Depos equipment, poor handling hygiene, and drinking water quality that has not yet matured.